Phosphine Oxide Catalyzed, Tetrachlorosilane-Mediated Enantioselective Direct Aldol Reactions of Thioesters - Rossi, Sergio; Annunziata, Rita; Cozzi, Franco; Raimondi, Laura Maria (Synthesis, 2015)
The stereoselective direct aldol reaction of S-phenyl thioesters and aromatic aldehydes promoted by tetrachlorosilane was realized for the first time; the proposed mechanism involves the formation of a chiral cationic hypervalent silicon species and requires the presence of catalytic amounts of a Lewis base, like a chiral phosphine oxide. The reaction affords syn β-hydroxy thioesters as major isomers in good yields, high diastereoselectivity (up to 99:1), and up to 92% enantiomeric excess. The absolute configuration of the major isomer was established by converting the product into the corresponding β-hydroxy ester. The scope of the reaction was also investigated by employing differently substituted thioesters in combination with different aromatic aldehydes.
Keywords: asymmetric catalysis; direct aldol reaction; hypercoordinate silicon; phosphine oxides; thioesters